Relationship between Emotional Stability, Motivation, and Online Learning Skill of First-Year Undergraduates Learning Online During COVID-19 Pandemic - Mohd Tajudin Md Ninggal ,; Nor Ezdianie Omar,; Rohaizak Omar ,; Azleen Ismail, (ASEAN Journal of Open and Distance Learning, 2020)
This study examined the relationship between the emotional stability, motivation, and online study skills of first-year undergraduate students at a public university in the east coast of Malaysia who studied online at home during the COVID-19 pandemic. The main objective of the study was to seek better understanding on the level of online study skills, motivation, and emotional stability of new undergraduate students who were engaged in online learning. A total of 159 students selected through purposive sampling participated in the online survey. They answered two sets of instruments, the Learner Personality Profile and Online Learning Skill, which consisted of 60 items and 30 items respectively. Both instruments were measured based on a five-point Likert scale. The Learner Personality Profile scale comprised (1) never, (2) rarely, (3) sometimes, (4) very often, and (5) always responses, while the Online Learning Skill scale consisted of (1) strongly disagree, (2) disagree, (3) neither agree nor disagree, (4) agree, and (5) strongly agree responses. The findings of the study showed that female students’ level of motivation scores (mean=3.90) were higher than male students’ scores (mean=3.61) based on a three-level range of mean scores (low=1.00 to 2.33, average=2.34 to 3.67, and high=3.68 to 5.00). Female students’ level of online study skills scores (mean=3.90) were also reported to be higher than male students’ scores (mean=3.61). However, both male and female students reported a low level of emotional stability scores (mean=2.20 and mean=2.19 respectively). The correlation analyses showed a significant relationship between online study skills and emotional stability, and between motivation and emotional stability. Curiously, the motivation variable did not act as a mediating factor in the relationship between online study skills and emotional stability based on the multiple-regression analysis. (Abstract by authors)